(3GdLGeY GdUMjMs - (3eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, CHh YHO Gddg , J (B256 (3g` s
(3ChdgG (B:s
(3HGH GdQLe HGdeUdi MOKfG YHO GdQGRb CNHQfG eYeQ Yf GdRgQi Yf CHj SdeI Yf LGHQ QVi Gddg Yfg Cf QLdG ef CSde LGA GdfHi Udi Gddg Ydjg hSde aGYJQa HGdRfG s
(3BNQgG (B:s
(3BNQ GdLRA GdYGTQ ef UMjM GdHNGQi HJeGeg Je cJGH GdLGeY GdUMjMq s
(3ai BNQ GdfSNI GdfSNI hQbJGf ajgeG YOO MOjK GdLGeY GdUMjMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B258s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B541s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdMOjK h GdeUWdMs